Interactions between Bacteria and Bile Salts in the Gastrointestinal and Hepatobiliary Tracts - Urdaneta, Verónica; Casadesús, Josep (Frontiers in Medicine, 2017)
Bile salts and bacteria have intricate relationships. The composition of the intestinal pool of bile salts is shaped by bacterial metabolism. In turn, bile salts play a role in intestinal homeostasis by controlling the size and the composition of the intestinal microbiota. As a consequence, alteration of the microbiome-bile salt homeostasis can play a role in hepatic and gastrointestinal pathological conditions. Intestinal bacteria use bile salts as environmental signals and in certain cases as nutrients and electron acceptors. However, bile salts are antibacterial compounds that disrupt bacterial membranes, denature proteins, chelate iron and calcium, cause oxidative damage to DNA, and control the expression of eukaryotic genes involved in host defense and immunity. Bacterial species adapted to the mammalian gut are able to endure the antibacterial activities of bile salts by multiple physiological adjustments that include remodeling of the cell envelope and activation of efflux systems and stress responses. Resistance to bile salts permits that certain bile-resistant pathogens can colonize the hepatobiliary tract, and an outstanding example is chronic infection of the gall bladder by Salmonella enterica. A better understanding of the interactions between bacteria and bile salts may inspire novel therapeutic strategies for gastrointestinal and hepatobiliary diseases that involve microbiome alteration, as well as novel schemes against bacterial infections.